The Utilization of Vindes Social Media as a Visual Communication Case Study of Vindes Sport Content - Shabrina Maghfirah, Inez; Edhy Aruman, Ahmad (LPPM Universitas PGRI Sumatera Barat, 2024)
In recent years, there has been a rapid increase in the use of social media in Indonesia and the world. Vindes Media is a digital platform that seeks to provide informative and entertaining content, providing space for the young generation to empower their aspirations, collaborate with each other, and contribute to the creative, sports and arts industries. This research aims to provide insight into effective communication with audiences interested in the world of sports. This research uses qualitative methods by utilizing Harold D. Lasswell's communication theory which describes communication through the question